Countryside Tourism in Orissa: An Economic Growth Engine (International Journal of Innovative Research in Engineering & Management, 2021)
In past few years, as tourism has grown in popularity  throughout the globe, a greater emphasis has been placed on  countryside tourism. Countryside tourism is now the centre of  interest all across the globe and it is increasingly identified as  a crucial driver of rural economic development. Tourism is the  2nd highest revenue-giving sector in the world, behind the oil  industry. As a result, the nation must distinguish between  various kinds of visitors in order to comprehend and analyze  the purpose of their presence. As a result, rural tourism has a  lot of promise and may generate a lot of money in the near  future. The primary goal of this article is to investigate the  advantages and drawbacks of rural tourism in Orissa. The  nature of this work is descriptive. The comprehensive research  approach was used to continue this study and to determine the  goals. Research papers, accessible literary materials, scholarly  publications, cases, and other published and unpublished  resources on the subject were used to gather pertinent and  supporting data. According to the research, rural tourism or  eco-tourism, if professionally organized, promoted, and  administered, may enhance the living conditions of the local  people while also helping the protection of the natural  environment. While tourism has evolved as a burgeoning  sector in Orissa, the issue now is to maximize the benefits of  the scenario by making the most use of the natural resources  available.
Keywords: Business Planning; Countryside Tourism; Economic Growth; Employment Generation; Rural Tourism